EFFECT OF CURING REGIMES ON STRENGTH OF GEOPOLYMER MORTARS BASED ON FLY ASH AND METAKAOLIN (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
Geopolymer materials have garnered significant attention as sustainable alternatives to traditional Portland cement-based materials. This study explores the effect of various curing regimes on the compressive strength (at 7 and 28 days) and flexural strength (at 28 days) of geopolymer mortars composed of fly ash (FA) and metakaolin (MK) in varying proportions. Four mixes were used: 100% FA; 60% FA+ 40% MK; 50% FA+10% OPC+ 40% MK; and 100% OPC. The binders were activated using 15% sodium silicate (solid content) with an alkali modulus (Ms = SiO2/Na2O) equal to 1. The curing conditions included ambient curing and elevated temperature curing at 80 °C under different setups. The results demonstrate that the curing regime significantly influences the mechanical properties of alkali-activated mortars (AAMs). Where, the results showed that heat curing regime enhanced the flexural, early-age compressive strength and the microstructure, in comparison with other regimes. The findings provide valuable insights into optimizing curing practices for geopolymer mortars to achieve desired mechanical properties. Replacing 40% of fly ash with metakaolin improved the microstructure of the matrix and decreased micro-cracks.